A Case Report of Embryonal Botryoid Rhabdomyosarcoma of the Uterine Cervix in a 26- Year-Old Woman - Ziyadova, Gunel; Kavuncuoglu, Altan; Ozten, Gonca; Tuncer, Zafer Selcuk (Gynecology Obstetrics & Reproductive Medicine, 2020)
Botryoid rhabdomyosarcoma originating from the cervix is rare among fertile women and constitutes 0.2% of all uterine cancers. A 26-year-old female patient with a cervical polyp presented with a case of sarcoma botryoides. The biopsy specimen confirmed the botryoid sarcoma of the uterine cervix and the patient underwent definitive surgery with lymphadenectomy. Pathology showed negative margins and total extraction of tumor. The tumor was confined to the cervix. The patient is considered group 1A in Intergroup RMS Working Group V (IRSG) criteria and the treatment plan continued with adjuvant vincristine, actinomycin D, cyclophosphamide chemotherapy. In the case of cervical polyps in the fertile age, the specimen must be carefully and histologically examined to rule out genital rabdomyosarcoma. Since the stage is a very important prognostic factor, an early diagnosis is crucial.